PENGARUH DAU, DBH DAN DERAJAT DESENTRALISASI TERHADAP RUANG FISKAL PEMERINTAH KABUPATEN DAERAH TERTINGGAL - Slamet Widodo; Rastri Paramita (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2018)
Considering the high level of dependence on transfer funds from the central government, underdeveloped regions need a separate policy approach that is not only based on capacity and fiskal needs alone, but also policies to cover all effort to increase the degree of decentralization of underdeveloped regions to manage their economy independently. The purpose of this study is to analyze the effect of General Allocation Funds (DAU), Revenue Sharing Funds (DBH) and Degrees of Decentralization on Fiskal Space Index in 112 underdeveloped regions for 2012-2016 period. Data used taken from BPS, the Ministry of Finance, and other relevant agencies. Analysis tools using Data Panel regression with Fixed Effect Model. The results of the analysis shows that all variables have a significant positive effect on fiskal space.